DEVELOPING DIFFERENTIATED TIERED NARRATIVE TEXTS IN ELEMENTARY INDONESIAN LANGUAGE LEARNING - Ninis Khoirunisa; Diah Gusrayani; Dadan Djuanda (Jurnal Cakrawala Pendas, 2025)
The diverse levels of reading comprehension skills often become an obstacle in the learning process at the elementary school level. Learning cannot be standardized but must accommodate student diversity, in line with the Merdeka Belajar concept in the Merdeka Curriculum. In this curriculum, differentiated instruction is promoted as an effective solution to address such challenges. This study aims to examine the feasibility and effectiveness of leveled narrative texts in differentiated instruction based on learning readiness. The research was conducted with 27 fourth-grade students at a public elementary school in Majalengka Regency, West Java, employing a Design and Development (D&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Differentiation was applied to the learning content by developing leveled narrative texts for low, medium, and high groups, determined through a diagnostic test of narrative text comprehension. Expert validation confirmed that the developed teaching materials were feasible to use. The implementation results showed that 93% of students achieved the learning objectives, with an average score of 81.3 in the final evaluation. These findings highlight that leveled narrative texts integrated into differentiated instruction are effective in supporting students’ reading comprehension skills and can serve as a strategic alternative for literacy learning in elementary schools.